2021
DOI: 10.1088/2053-1591/ac2404
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the mechanical and tribological properties of polyethylene wax/silicone rubber composites

Abstract: As an auxiliary agent for rubber processing, polyethylene wax can be used to enhance the diffusion of filler in rubber, improve the extrusion speed of rubber compound and facilitate rubber demoulding, which has good development potential in the field of rubber processing and manufacturing. At present, there is no research on the optimum amount of polyethylene wax in silicone rubber. Therefore, in this paper, we studied the influence of different amount of polyethylene wax on the mechanical and friction propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Owing to its lubricating property, PE wax can be utilized as lubricating additives in ultra‐high molecular weight polyethylene (UHMWPE) films, [ 29 ] which achieved a low COF value (0.05–0.20) similar to PTFE. Liang et al [ 30 ] mechanical mixed the PE wax with silicone rubber to fabricate the composites through the hot‐pressing process. They found that PE wax can be exfoliated from the rubber matrix, dispersed on the friction surface during friction, and significantly reduced COF at the optimal amount of 0.25 phr.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its lubricating property, PE wax can be utilized as lubricating additives in ultra‐high molecular weight polyethylene (UHMWPE) films, [ 29 ] which achieved a low COF value (0.05–0.20) similar to PTFE. Liang et al [ 30 ] mechanical mixed the PE wax with silicone rubber to fabricate the composites through the hot‐pressing process. They found that PE wax can be exfoliated from the rubber matrix, dispersed on the friction surface during friction, and significantly reduced COF at the optimal amount of 0.25 phr.…”
Section: Introductionmentioning
confidence: 99%